2021
DOI: 10.1038/s41598-021-00252-3
|View full text |Cite
|
Sign up to set email alerts
|

A national and sub-national metaregression of the trend of insufficient physical activity among Iranian adults between 2001 and 2016

Abstract: Insufficient physical activity (IPA) caused approximately 5% of mortalities in 2017 in Iran, almost double its global average. Despite the relatively considerable burden, a knowledge gap exists regarding the trend of IPA in recent years. We described the trend of IPA prevalence utilizing the data from six rounds of STEPwise approach to risk factor Surveillance (STEPS) in Iran. We estimated the physical activity status of Iranian adults from 2006 to 2016 after adjusting for years of schooling, urbanization perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The findings of our study are similar to related studies in Iran. Based on the STEPwise approach to risk factor Surveillance (STEPS) in Iran, the prevalence of insufficient physical activity was reported at 55.4% in 2016 [ 56 ]. Food insecurity prevalence was reported at 18.3% in East Asia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our study are similar to related studies in Iran. Based on the STEPwise approach to risk factor Surveillance (STEPS) in Iran, the prevalence of insufficient physical activity was reported at 55.4% in 2016 [ 56 ]. Food insecurity prevalence was reported at 18.3% in East Asia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of physical inactivity and food insecurity is relatively high among Iranian people, which is concerning and requires attention from policymakers [ 56 , 75 ]. Interventions improving social capital may be beneficial in this regard, as we found that more robust social capital is associated with higher physical activity levels and food security among a sample of Iranian people.…”
Section: Discussionmentioning
confidence: 99%
“…This causes or triggers medical conditions and non-communicable diseases related to insufficient PA in 1.4 billion individuals [ 4 ]. In Iran, the insufficient PA level has increased from 23.1% in 2001 to 55.4% in 2016, based on STEPwise Approach to NCD Risk Factor Surveillance (STEPS) surveys, and there is a need for urgent action [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noncommunicable diseases are one of the major causes of mortality worldwide, and in 2016, 40.5 million deaths were attributed to noncommunicable diseases. 1 Unhealthy behavior, such as smoking, excessive alcohol consumption, and physical inactivity, are the main risk factors for noncommunicable diseases, including cardiovascular diseases, cerebrovascular diseases, type 2 diabetes mellitus, breast cancer, obesity, hypertension, and colon cancer. 2 Among these, insufficient lifetime physical activity is a risk factor for multiple health conditions, such as diabetes, obesity, and cancers.…”
mentioning
confidence: 99%
“…Physical activity levels in Iran have declined from 2001 to 2016, while the prevalence of physical inactivity has doubled during this time. 1 Consequently, determining Iranians' lifetime physical activity levels is crucial to understand the domains contributing most to their insufficient activity levels and to guide researchers, policymakers, and stakeholders in developing future guidelines. 14,15 There is, however, no valid and reliable instrument to measure lifetime physical activity among Iranians.…”
mentioning
confidence: 99%